TRENDS IN ARTIFICIAL INTELLIGENCE IN THE PHILIPPINES FOR BIOMEDICAL ENGINEERING AND PUBLIC HEALTH EMERGENCY APPLICATIONS: A REVIEW (Innovative Technology and Management Journal, 2020)
Artificial Intelligence has been considered as one of the disruptive technologies for the past years, especially in the advent of the Fourth Industrial Revolution (4IR). As researchers continue to unlock the potentials of AI, the limits of what can be done with this technology are yet to be seen. As AI increases the productivity of companies such as those in manufacturing and business process outsourcing, it may also result in the displacement of workers. This is addressed by new job opportunities such as those related to data sciences. The Philippine government, through the Department of Science and Technology, has laid the foundation of AI infrastructure and continues building the Filipino scientists capacity but a law must be passed to coordinate efforts nationwide and ensure that the AI infrastructure is maximized to address priority areas such as boosting economy, better healthcare, and responding to public health emergencies.
Keywords: biomedical; artificial intelligence; public health